The relationship between social support and college students’ physical activity participation in China: the mediating effect of self-efficacy - Niu, Mingtian; Dong, Mingyuan; Shi, Panpan; Choi, Yongchul; Li, Ning (Frontiers in Psychology, 2025)
BackgroundWith the increasing health awareness among Chinese college students, the relationship between social support, self-efficacy, and participation in physical activities has become a focal point of research. Particularly in the context of gender differences, exploring how these factors influence college students’ exercise behaviors is significant.ObjectiveThis study aims to examine how social support influences college students’ self-efficacy and their participation in physical activities, and whether self-efficacy mediates this relationship. It should be noted that in the context of this study, college students are considered late adolescents or emerging adults, as defined in developmental psychology.MethodsA survey was conducted among 489 college students from universities in Henan Province, China. The survey included the Physical Activity Questionnaire (PAQ), the Social Support Scale, and the Exercise Self-Efficacy Scale (ESES). Exploratory factor analysis, linear regression analysis, and structural equation modeling were used to examine the relationship between social support and college students’ participation in physical activities.ResultsThe regression effects of social support on college students’ participation in physical activities (F = 47.898) and self-efficacy (F = 224.247) were significant (p < 0.01). Self-efficacy also significantly predicted participation in physical activities (F = 136.706, p < 0.01). Among female students, both the effect of social support (B = 0.177, t = 2.332*) and self-efficacy (B = 0.307, t = 5.810**) on participation in physical activities were significant. The mediating effect of self-efficacy accounted for 59.6% of the total effect, while the direct effect accounted for 40.4%.ConclusionTo promote female college students’ participation in physical activities, particular attention should be paid to the critical role of self-efficacy. At the same time, it is also important not to overlook the competitive sports preferred by male students, which require stronger self-efficacy to cope with competitive pressures and social expectations.